Auditoría de Gestión al Departamento de Talento Humano y Marketing de la Cooperativa de Ahorro y Crédito Cristo Rey, Periodo del 01 de Enero al 31 de Diciembre del 2014 - Ordóñez Jima, Karen Tatiana (2017)
The thesis entitled "MANAGEMENT AUDIT DEPARTMENT OF HUMAN TALENT AND MARKETING OF credit union CRISTO REY, PERIOD 01 JANUARY TO 31 DECEMBER 2014", was developed against the need or requirement of the authorities of the cooperative, with the overall objective: to conduct a management audit department Human Resource and Marketing, which will allow to evaluate the effectiveness of the process under study, in relation to its objectives and goals; to determine the degree of economy and efficiency in the use of resources and to measure the quality of services offered and the impact of its activities. From the conceptual perspective of the examination was necessary to implement a methodology that involves running five phases are as follows: First phase, preliminary knowledge, here the previous visit was conducted SWOT was established and a general diagnosis was obtained; The second phase of planning, internal control system is evaluated and tools for the next phase is prepared; EXECUTION The third phase is the implementation of programs and the preparation of working papers supporting the report; The fourth COMMUNICATION RESULTS phase, which aims to prepare and submit the final report; TRACKING The fifth phase of the findings and institutional commitment to make after a year. Likewise, the results obtained in the research work was determined that the Human Talent and Marketing department presents a poor internal control due to the inadequate organic structure, the lack of manuals of procedures, incongruous 5 recruitment and selection of personnel, there is no Training plan; Lack of control of staff attendance; In terms of Marketing, the instructions for products and services are not updated, finally for the development of their functions there is no adequate infrastructure, there is no proposal to provide functional locations to branches what should be raised by the Manager to The General Assembly of Members. Therefore it ends with the conclusions and recommendations aimed at correcting the findings in Human and Marketing Talent component, the recommendations are mainly addressed to the manager of the credit union "Cristo Rey" of the city of Loja